On an integral equation for the free boundary of stochastic, irreversible investment problems - Giorgio Ferrari (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
In this paper we derive a new handy integral equation for the free boundary of infinite time horizon, continuous time, stochastic, irreversible investment problems with uncertainty modeled as a one-dimensional, regular diffusion X0;x. The new integral equation allows to explicitly find the free boundary b(.) in some so far unsolved cases, as when X0;x is a three-dimensional Bessel process or a CEV process. Our result follows from purely probabilistic arguments. Indeed, we first show that b(X0;x(t)) = l L(t), with l L(t) unique optional solution of a representation problem in the spirit of Bank-El Karoui [4]; then, thanks to such identification and the fact that l L uniquely solves a backward stochastic equation, we find the integral problem for the free boundary.
urn:nbn:de:0070-pub-26740341
Keywords: C02; E22; D92; G31; 330; integral equation; free boundary; irreversible investment; singular stochastic control; optimal stopping; one-dimensional diffusion; Bank and El Karoui's Representation Theorem; base capacity